The IN.PACT DEEP Clinical Drug-Coated Balloon Trial: 5-Year Outcomes - Zeller, Thomas; Micari, Antonio; Scheinert, Dierk; Baumgartner, Iris; Bosiers, Marc; Vermassen, Frank E G; Banyai, Martin; Shishehbor, Mehdi H; Wang, Hong; Brodmann, Marianne (JACC. Cardiovascular interventions, 2020)
The goal of this study was to evaluate the 5-year follow-up data of the IN.PACT DEEP (Randomized IN.PACT Amphirion Drug-Coated Balloon [DCB] vs. Standard Percutaneous Transluminal Angioplasty [PTA] for the Treatment of Below-the-Knee Critical Limb Ischemia [CLI]) trial. Initial studies from randomized controlled trials have shown comparable short-term outcomes of DCB angioplasty versus PTA in patients with CLI with infrapopliteal disease. However, the long-term safety and effectiveness of DCB angioplasty remain unknown in this patient population. IN.PACT DEEP was an independently adjudicated prospective, multicenter, randomized controlled trial that enrolled 358 subjects with CLI. Subjects were randomized 2:1 to DCB angioplasty or PTA. Assessments through 5 years included freedom from clinically driven target lesion revascularization, amputation, and all-cause death. Additional assessments were conducted to identify risk factors for death and major amputation, including paclitaxel dose tercile. Freedom from clinically driven target lesion revascularization through 5 years was 70.9% and 76.0% (log-rank p = 0.406), and the incidence of the safety composite endpoint was 59.8% and 57.5% (log-rank p = 0.309) in the DCB angioplasty and PTA groups, respectively. The rate of major amputation was 15.4% for DCB angioplasty compared with 10.6% for PTA (log-rank p = 0.108). Given the recent concern regarding a late mortality signal in patients treated with paclitaxel-coated devices, additional analyses from this study showed no increase in all-cause mortality with DCB angioplasty (39.4%) compared with PTA (44.9%) (log-rank p = 0.727). Predictors of mortality included age, Rutherford category >4, and previous revascularization but not paclitaxel by dose tercile. Tibial artery revascularization in patients with CLI using DCB angioplasty resulted in comparable long-term safety and effectiveness as PTA. Paclitaxel exposure was not related to increased risk for amputation or all-cause mortality at 5-year follow-up. (Study of IN.PACT Amphirion™ Drug Eluting Balloon vs. Standard PTA for the Treatment of Below the Knee Critical Limb Ischemia [INPACT-DEEP]; NCT00941733).